Muscarinic Receptors Modulate the Intrinsic Excitability of Infralimbic Neurons and Consolidation of Fear Extinction - Santini, Edwin (Nature Publishing Group, 2012)
There is considerable interest in identifying pharmacological compounds that could be used to facilitate fear extinction. Recently, we showed that the modulation of M-type K(+) channels regulates the intrinsic excitability of infralimbic (IL) neurons and fear expression. As muscarinic acetylcholine receptors inhibit M-type K(+) channels, cholinergic inputs to IL may have an important role in controlling IL excitability and, thereby, fear expression and extinction. To test this model, we combined whole-cell patch-clamp electrophysiology and auditory fear conditioning. In prefrontal brain slices, muscarine enhanced the intrinsic excitability of IL neurons by reducing the M-current and the slow afterhyperpolarization, resulting in an increased number of spikes with shorter inter-spike intervals. Next, we examined the role of endogenous activation of muscarinic receptors in fear extinction. Systemic injected scopolamine (Scop) (muscarinic receptor antagonist) before or immediately after extinction training impaired recall of extinction 24-h later, suggesting that muscarinic receptors are critically involved in consolidation of extinction memory. Similarly, infusion of Scop into IL before extinction training also impaired recall of extinction 24-h later. Finally, we demonstrated that systemic injections of the muscarinic agonist, cevimeline (Cev), given before or immediately after extinction training facilitated recall of extinction the following day. Taken together, these findings suggest that cholinergic inputs to IL have a critical role in modulating consolidation of fear extinction and that muscarinic agonists such as Cev might be useful for facilitating extinction memory in patients suffering from anxiety disorders.